Under the hood: the mechanics of London's street gangs - Densley, J; James Andrew Densley (2011)
Based upon two years of ethnographic fieldwork in London, England, which incorporated nearly 200 interviews with gang members, gang associates, and police officers, among others, this thesis addresses three questions presently unresolved in the street gangs literature: What is the business of gangs? How are gangs organised? And how do gangs recruit? With regard the business of gangs, this thesis illustrates how recreation, crime, enterprise, and extra-legal governance represent sequential stages in the evolutionary cycle of London’s street gangs. Gang member testimony emphasises how gangs typically begin life as neighbourhood-based peer groups, but also how, in response to external threats and financial commitments, gangs grow to incorporate street-level drugs distribution businesses that very much resemble the multi-level marketing structure of direct-sales companies. People join gangs to make money, achieve status, and obtain protection. Gangs engage in turf wars, acquire violent resources, and develop hierarchical structures in order to maintain provision of these desirable goods and services. Gang organisation, in turn, becomes a function of gang business. To better understand the nature and extent of gang organisation, this thesis moves on to discuss the presence of subgroups, hierarchy and leadership, pecuniary and non-pecuniary incentives, rules, responsibilities, and restrictions, and consequences for absconding within gangs. It further presents how, in order to convey reputation and achieve intimidation, gangs seek association with elements of popular culture that help promote their image. Finally, through the novel application of signalling theory to the gang recruitment process, this thesis demonstrates how gangs face a primary trust dilemma in their uncertainty over the quality of recruits. Given that none of the trust-warranting properties for gang membership can be readily discovered from observation, gangs look for observable signs correlated with these properties. Gangs face a secondary trust dilemma in their uncertainty over the reliability of signs because certain agents (e.g., police informants, rival gang members, and adventure-seekers) have incentives to mimic them. To overcome their informational asymmetry gangs thus screen for signs that are too costly for mimics to fake but affordable for the genuine article. The thesis concludes with a discussion of gang desistance and intervention in the context of escalating youth violence in London.